2019
DOI: 10.1186/s40662-019-0149-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dry eye disease in newly diagnosed anxiety and depression patients using anterior segment optical coherence tomography

Abstract: Background We aimed to evaluate dry eye diseases (DED) in patients with newly diagnosed depression and anxiety patients. Methods Forty newly diagnosed depression, 35 anxiety patients, and 37 controls without any history of taking psychiatric drugs (or before the beginning of psychiatric medication) and topical ophthalmic drop use, were included in the study. All depression and anxiety diagnoses were performed by an experienced psychiatrist. Beck depression and anxiety t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
1
14
2
Order By: Relevance
“…A review by McMonnies (29) also showed that dry eye features in patients with mental disorders were mostly severe symptoms and relatively mild signs. In addition, other studies have found that patients with depression, anxiety, and obsessivecompulsive disorder had more severe signs and symptoms of DED than the controls (11,30). Unlike previous studies, our study involved patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 94%
“…A review by McMonnies (29) also showed that dry eye features in patients with mental disorders were mostly severe symptoms and relatively mild signs. In addition, other studies have found that patients with depression, anxiety, and obsessivecompulsive disorder had more severe signs and symptoms of DED than the controls (11,30). Unlike previous studies, our study involved patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, depression could also increase the symptom of MGD. Ulusoy et al 15 invited 40 newly diagnosed depression patients and found that patients without a history of psychiatric drug use showed dry eye symptoms. Some studies revealed that negative emotional states would induce or enhance the perception of pain and irritation 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Mental health problems have been identified as potential risk factors of DED [31][32] . The COVID-19 pandemic has been shown to increase the incidence of mental health problems, among the [33][34] .…”
Section: Discussionmentioning
confidence: 99%